2008
DOI: 10.1080/17457300802292439
|View full text |Cite
|
Sign up to set email alerts
|

Homicide death in Dar es Salaam, Tanzania 2005

Abstract: Violence disproportionately affects low- and middle-income countries. Deeper understanding is needed in areas where little research has occurred. The objectives of the study were to: (a) ascertain rate of homicide death; (b) describe the victims and circumstances surrounding their deaths in Dar es Salaam, Tanzania in 2005. This study was developed by adapting the WHO/CDC Injury Surveillance Guidelines (Holder et al., 2001). Data on 12 variables were collected on all homicide deaths. Descriptive statistics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 5 publications
3
23
0
Order By: Relevance
“…The psychiatrist provides adequate care and supervision during and after surgical treatment [9,11,14,15]. However, in most developing countries such as Tanzania, late presentation to health facilities coupled with lack of advanced pre-hospital and ineffective ambulance system for transportation of patients to hospital care contributes significantly to increasing morbidity and mortality [9,16,17]. …”
Section: Introductionmentioning
confidence: 99%
“…The psychiatrist provides adequate care and supervision during and after surgical treatment [9,11,14,15]. However, in most developing countries such as Tanzania, late presentation to health facilities coupled with lack of advanced pre-hospital and ineffective ambulance system for transportation of patients to hospital care contributes significantly to increasing morbidity and mortality [9,16,17]. …”
Section: Introductionmentioning
confidence: 99%
“…Frequency distributions, means, standard deviations, proportions, and ratios were selected as appropriate for each variable. Data on the identified bodies have been reported elsewhere (Outwater et al, 2008). For this research note, data were analyzed focusing on the adults who were buried by the city (Unknowns).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, quantitatively, the DSM homicide surveillance of 2005 found that the age adjusted homicide rate was 12.57 per 100,000 population (males and females, 22.26 and 2.65, respectively; Outwater et al, 2008). The gender gap was 14:1.…”
mentioning
confidence: 99%
See 2 more Smart Citations